The Impact of Teaching Islamic Jurisprudence Using the Strategy of What Do I Know? What Do I Want to Learn? and What Did I Learn? on the Academic Achievement and Development of Critical Thinking Skills among Second-Grade Intermediate Students - Al-Asbali, Rashid Fayez; Al-Shamti, Omar AbdulQadir (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the impact of teaching Islamic jurisprudence using the strategy of what do I know? what do I want to learn? and what did I learn? on the academic achievement among second-grade intermediate students and identify the impact of teaching Islamic jurisprudence using the strategy of what do I know? what do I want to learn? and what did I learn? on the development of critical thinking skills among second-grade intermediate students. The study followed the experimental method and the study sample was limited to second intermediate students in two schools that were randomly chosen. One school represented the experimental group with (21) students and the other represented the control group with (20) students; therefore, the total number of students in the research sample is (41) students. The study will depend on the achievement test and the critical thinking skills test as the study instruments. The study came out with the following results: The students of the experimental group who studied following the strategy of what I know? What do I want to learn? what did I learn? showed better results in the academic achievement and development of critical thinking skills in the students of the control group who studied following the usual approach. The results also showed the positive impact of the strategy what do I know? what do I want to learn? what did I learn? on the academic achievement and development of critical thinking skills among the students of the experimental group. In light of the previous results, the study recommended holding training courses for jurisprudence teachers to train them on the use of the strategy what do I know? what do I want to learn? and what did I learn? in teaching. Also, the study recommended using the strategy what do I know? what do I want to learn? what did I learn? in teaching the subjects of Sharia studies in general and the subject of Islamic jurisprudence in particular due to its positive impact on teaching.
Keywords: Jurisprudence; Strategy What do I know; What do I want to learn; what did I learn; Academic Achievement; Critical Thinking Skills; Second; Grade Intermediate Students